Resilience and the population history of the Kuril Islands, Northwest Pacific: A study in complex human ecodynamics. (17th October 2016) - Fitzhugh, Ben; Gjesfjeld, Erik W.; Brown, William A.; Hudson, Mark J.; Shaw, Jennie D.
Abstract: Living in remote places can strain the adaptive capacities of human settlers. It can also protect communities from external social, political and economic forces. In this paper, we present an archaeological population history of the Kuril Islands. This string of small volcanic islands on the margins of the Northwest Pacific was occupied by maritime hunting, fishing and gathering communities from the mid-Holocene to recent centuries. We bring together (1) 380 new and previously published archaeological radiocarbon dates, (2) a new paleodemographic model based on a radiocarbon-timestamped temporal frequency distribution of archaeological deposits, (3) recently published paleoclimate trends, and (4) recently published archaeological proxy evidence for changes in the extent of social networks. We demonstrate that, over the last two millennia, inhabitants of the Kuril Islands underwent dramatic demographic fluctuations. Explanations of these fluctuations are considered in the context of environmental hazards, social networks and the emergence of an East Asian "World System", elucidating the tension between local and external adaptive strategies to social and ecological uncertainty. Results suggest that population resilience to local climate and environmental variability was achieved by virtue of social networks that maintained non-local support in times of crisis. Conversely, the expansion of the East Asian political economy into neighboring regions of the southern margin of the Kuril Islands perhaps in conjunction with exposure to epidemic diseases appears to have undermined the adaptive strategies, resulting in an increase in the vulnerability of Kuril populations to environmental fluctuations.